Prospective superficial EPR in-vivo dosimetry study during hypofractionated radiotherapy of breast cancer patients treated with helical tomotherapy - Sebastian Höfel; Matteo Gandalini; Michael K. Fix; Malte Drescher; Felix Zwicker (Radiation Oncology, 2021)
Abstract Background In-vivo dosimetry (IVD) is a patient specific measure of quality control and safety during radiotherapy. With regard to current reporting thresholds for significant occurrences in radiotherapy defined by German regulatory authorities, the present study examines the clinical feasibility of superficial electron paramagnetic resonance (EPR) IVD of cumulative total doses applied to breast cancer patients treated with helical intensity-modulated radiotherapy (tomotherapy). Methods In total, 10 female patients with left- or right-sided breast cancer were enrolled in this prospective IVD study. Each patient received a hypofractionated whole breast irradiation. A total median dose of 42.4 Gy in 16 fractions (5 fractions per week) was prescribed to the planning target volume. The treatments were completely delivered using helical tomotherapy and daily image guidance via megavoltage CT (MVCT). For each patient, three EPR dosimeters were prepared and placed at distinct locations on the patient’s skin during the delivery of all fractions. Two dosimeters were placed next to the ipsilateral and contralateral mammilla and one dosimeter was placed ventrally to the thyroid (out-of-primary-beam). The total doses delivered to the dosimeters were readout after all fractions had been administered. The measured total dose values were compared to the planned dose values derived from the treatment planning system (TPS). Daily positional variations (displacement vectors) of the ipsilateral mammilla and of the respective dosimeter were analyzed with respect to the planned positions using the daily registered MVCT image. Results Averaged over all patients, the mean absolute dose differences between measured and planned total dose values (± standard deviation (SD)) were: 0.49 ± 0.85 Gy for the ipsilateral dosimeter, 0.17 ± 0.49 Gy for the contralateral dosimeter and -0.12 ± 0.30 Gy for the thyroid dosimeter. The mean lengths of the ipsilateral displacement vectors (± SD) averaged over all patients and fractions were: 10 ± 7 mm for the dosimeter and 8 ± 4 mm for the mammilla. Conclusion Superficial EPR IVD is suitable as additional safeguard for dose delivery during helical tomotherapy of breast cancer. Despite positional uncertainties in clinical routine, the observed dose deviations at the ipsilateral breast were on average small compared to national reporting thresholds for total dose deviations (i.e. 10%/4 Gy). EPR IVD may allow for the detection of critical dose errors during whole breast irradiations.